S3‐Leitlinie „Aktinische Keratose und Plattenepithelkarzinom der Haut“ - Kurzfassung, Teil 1: Diagnostik, Interventionen bei aktinischen Keratosen, Versorgungsstrukturen und Qualitätsindikatoren = S3 guideline for actinic keratosis and cutaneous squamous cell carcinoma – short version, part 1 : diagnosis, in-terventions for actinic keratoses, care structures and quality-of-care indicators - Heppt, Markus V.; Leiter, Ulrike; Steeb, Theresa; Amaral, Teresa; Bauer, Andrea; Becker, Jürgen C.; Breitbart, Eckhard; Breuninger, Helmut; Diepgen, Thomas L.; Dirschka, Thomas; Eigentler, Thomas; Flaig, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Actinic keratoses (AK) are common lesions in light-skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence-based framework for clinical decision making, the guideline “actinic keratosis and cutaneous squamous cell carcinoma” was developed using the highest level of methodology (S3) according to regulations issued by the Association of Scientific Medical Societies in Germany (AWMF). The guideline is aimed at dermatologists, general practitioners, ENT specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office-based settings as well as other medical specialties involved in the diagnosis and treatment of patients with AK and cSCC. The guideline is also aimed at affected patients, their relatives, policy makers and insurance funds. In the first part, we will address aspects relating to diagnosis, interventions for AK, care structures and quality-of-care indicators.
Gesehen am 20.04.2020